Factors Influencing Sustainable Banking Development: A Case Study of Commercial Banks in Vietnam - Lu Phi Nga; Tam Phan Thanh (Ianna Journal of Interdisciplinary Studies, 2024)
Background: Sustainable banking development is crucial for financial institutions' long-term viability and profitability, particularly in an era of increasing global environmental awareness and regulatory pressures. Understanding the factors that influence sustainable banking is essential for banks aiming to enhance their sustainability practices and gain a competitive edge.